QUANTITATIVE ROADMAP: EXPLORING METHODOLOGY THROUGH THE LENS LITERATURE REVIEW - Leni Juniarti; Donna Boedi Maritasari; Dinda Rizka Amalia; Nurul Aini (PT. Jurnal Center Indonesia Publisher, 2025)
Quantitative research is a crucial foundation in the scientific landscape to understand phenomena objectively and measurably. Although essential, there is often a gap between methodological idealism and research practice, especially among novice researchers, which is indicated by the use of quantitative methods that are not optimal in student theses due to lack of mastery of methodology and statistics, marked by inconsistencies in variable logic, lack of theoretical basis, data bias, sampling technique errors, to inaccuracy in testing the validity of instruments and statistical analysis. Through a systematic and comprehensive literature review, this article aims to present a complete picture of the “roadmap” of quantitative research, including the essence, principles, key stages (starting from problem formulation, sample determination, instrument development, data collection, to analysis and interpretation of results), and its various types, rooted in the positivist paradigm that emphasizes objectivity and hypothesis testing. Although quantitative research offers significant advantages such as time efficiency and generalizability, challenges such as difficulty in data collection and lack of in-depth analysis also need to be overcome, so improving methodological and statistical training is crucial to producing valid, accountable scientific work that contributes significantly to the development of science.